2009
DOI: 10.1111/j.1525-1470.2009.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Congenital Linear Eccrine Spiradenoma

Abstract: Eccrine spiradenoma (ES) is a benign uncommon tumor of skin adnexa with a characteristic clinical and histopathological presentation. Typically, it presents as a painful, slow growing and solitary nodule on the head or upper trunk in adult patients. We report a child with linear ES which presented with asymptomatic papulonodular lesions in a blaschkoid distribution on the face. Cases reported in the literature of multiple spiradenomas are very rare and multiple linear lesions are even rarer. To date, 21 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Neonatal spiradenoma is rare. A research of the literature revealed only five reported cases (2,5,6). They can present at birth as solitary or multiple, asymptomatic papulonodules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal spiradenoma is rare. A research of the literature revealed only five reported cases (2,5,6). They can present at birth as solitary or multiple, asymptomatic papulonodules.…”
Section: Discussionmentioning
confidence: 99%
“…They can present at birth as solitary or multiple, asymptomatic papulonodules. Malignant transformation is uncommon and mostly occurs in tumors that have been present for many years with no age, sex, or site predilection, and more often in multiple spiradenomas (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple spiradenomas are assumed to originate from pluripotent stem cells in the folliculosebaceous‐apocrine unit during embryogenesis 2 . Familial cases of multiple localized spiradenomas have also been reported, suggesting that genetic predispositions such as germ cell mutations or mosaicism are present in such cases 4 …”
Section: Figurementioning
confidence: 99%
“…Of these, only 6 case reports developed along Blaschko's lines, as in our case (Table 1). [4][5][6][7][8][9] None of these reported cases underwent genetic testing for ALPK1 mutation.…”
mentioning
confidence: 99%
See 1 more Smart Citation